Analysis of Mechanism of Formation of Interference at the Output Multilevel Finite State Machine - Y. A. Nikitin (Известия высших учебных заведений России: Радиоэлектроника)
A single model for the formation of two-level and multi-level oscillations with envelopes of different shapes using the methods of passive digital frequency synthesis are considered. A comparative analysis of the spectra of oscillations at the output of the system of two-level and multilevel passive digital frequency synthesis is made. The mechanisms of interference generation in the spectrum of the output oscillations with multilevel frequency synthesis are analyzed for the case of the perfect output digital-to-analog converter (DAC), with the bit width fractional multiple to the bit width of the phase accumulator (FA). It is also shown that additional spectral components appear, which are absent at the integral bit width relation of DAC and FA.